ChemInform Abstract: [Et3NH][HSO4]‐Catalyzed Eco‐Friendly and Expeditious Synthesis of Thiazolidine and Oxazolidine Derivatives. Issue 29 (July 2015) - Malla, Ali Mohammed; Parveen, Mehtab; Ahmad, Faheem; Azaz, Shaista; Alam, Mahboob
Abstract The title compounds are obtained by one‐pot three‐component reaction of cyclic diketones (I), cyanates (II) or (V) or (VII), and ethyl chloroacetate (III) under solvent‐free, mild, and environmentally benign conditions.